The divergent effects of moderate climate warming on the gut microbiota and energetic state of cold-climate lizards from open and semi-closed microhabitats - Liu, Wanli; Yang, Jing; Meng, Yu; Wu, Danyang; Cui, Luoxin; Li, Teng; Sun, Baojun; Liu, Peng (Frontiers in Microbiology, 2022)
Understanding the physiological responses to warming temperatures is critical for evaluating the vulnerabilities of animals to climate warming. The physiological responses are increasingly affected by gut microbiota. However, the interactions between physiological responses and the gut microbiota of sympatric animals from various microhabitats in the face of climate change remain largely unknown. To evaluate the effects of warming temperatures on animals from different microhabitats, we compared locomotor performance, metabolic rate, growth, survival, and gut microbiota of two sympatric ectothermic species (Eremias argus and Takydromus amurensis) from open and semi-closed microhabitats under present and moderate warming climate conditions, respectively. We found that locomotor performance and growth rates of snout-vent length (SVL) were enhanced in both lizard species by warming climate. Interestingly, warming temperatures enhanced resting metabolic rates (RMR) in the open-habitat lizard, E. argus, but depressed them in the semi-closed habitat lizard, T. amurensis. Reversely, the metabolism-related gut microbiota was not affected by warming in E. argus, whereas it was significantly enhanced by warming in T. amurensis, indicating a plausible compensatory effect of the gut microbiota on the metabolic regulation of T. amurensis. Furthermore, warming likely improved immunity in both lizard species by significantly reducing pathogenic bacteria while increasing probiotics. This study found that high-latitude sympatric lizards from both open and semi-closed habitats were beneficial to warming temperatures by physiological modification and regulation of the gut microbiota and highlighted the importance of integrating the physiology and gut microbiota in evaluating the vulnerability of animals to climate warming.